The Differences on the Grammar Learning Strategies Used Based on the Students’ Gender Perspective - FITRI, GESNA; YUNITA, WISMA; HARAHAP, ALAMSY AH (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Learning grammar is an essential thing in learning new language and a strategy in learning grammar is needed to cope with it. The research aimed to investigate the grammar learning strategy that was used by English students at Muhammadiyah University of Bengkulu based on the gender. A quantitative reseach design was carried out to collect and analyse the data. The participants were 37 male and 96 female English students who studied at the English education study program of Muhammadiyah University of Bengkulu. The data were collected by using questionnaire and they were analysed quantitatively. The result revealed that there was the difference strategy used by male and female students in learning grammar. The male students tended to use the Cognitive strategy meanwhile the female students preferred to use the social strategies. Based on the result, it was concluded that the English students seemed to choose the grammar learning strategy based on their interest to enhance their grammatical competency.